UNIT 20C.2 Purification Toxoplasma gondii Tissue Cysts Using Percoll Gradients. Issue 1 (16th May 2017) - Watts, Elizabeth A.; Dhara, Animesh; Sinai, Anthony P.
Abstract : The protozoan parasite Toxoplasma gondii is capable of infecting all warm‐blooded animals and humans. Infectious, transmissible forms of the parasite include oocysts produced by the sexual cycle within the definitive feline host and tissue cysts that form Toxoplasma in the central nervous system and muscle during the asexual cycle within all chronically infected warm‐blooded hosts. These tissue cysts are populated with slow‐growing bradyzoites, which until recently have been thought to be dormant entities in the context of immune sufficiency. Reactivation to active growth during immune suppression is of critical clinical importance. However, little is known about tissue cysts or the bradyzoites they house, as the diversity of tissue cysts cannot be replicated in cell culture systems. This protocol for optimization of tissue cyst purification from the brains of infected mice using Percoll gradients provides an efficient means to recover in vivo–derived tissue cysts that can be applied to imaging, cell biological, biochemical, transcriptomic, and proteomic analyses. © 2017 by John Wiley & Sons, Inc.